Hijab and modesty: Muslim religious identity expression among Egyptian women in the United States. Issue 2 (1st June 2019) - Shaheen, Manal; Hwang, Chanmi
This study explored the symbolic meaning of modest dress, generally referred to as hijab, to Egyptian Muslim women living in the United States. In the diaspora, women need to integrate the requirements for religious modesty when shopping for western apparel that is not designed to align with their values of modesty. Face-to-face, in-depth interviews with photo-elicitation were conducted with ten veiled Muslim women to explore the symbolic meaning of hijab and their views on modest clothing as it relates to religiosity. Three themes surfaced as the participants discussed their experiences: (1) intrinsic and extrinsic values of hijab – adapting to US norms, (2) the accessibility and attributes of modest clothing and (3) defining modest hijab based on religiosity – three types. The findings of this study may help non-Muslims understand the symbolic message of hijab and the different types of modest clothing related to religiosity.